The influence of land use and land cover change on stormwater runoff in a highly urbanizing catchment. A case of Msimbazi catchment in Dar es Salaam city, Tanzania (ҚазҰУ Хабаршысы. География сериясы, 2021)
A hydrological pattern of any catchment is highly affected or determined by how land is being used within the particular catchment. Other determining factors may include but not limited to climatic condition as well as the catchment size. This study investigated the potential effects of land use/land cover changes on stormwater runoff in a highly urbanizing catchment, for a case of Msimbazi catchment in Dar es Salaam, Tanzania. Three different years (1998, 2009 and 2018) were selected and used as case studies. The extreme, more than 50-year rainfall event of December 2011 was used to develop the meteorological model in HEC-HMS. An engineering solution towards handling the generated stormwater runoff is also proposed. ArcGIS, HEC-Geo HMS and HEC-HMS model were used for an event-based rainfall-runoff simulation. The computed peak discharge showed an increase of about 23.08% from 1998 to 2018. The peak inflows for all the detention basins were observed in the extreme event of 20 December 2011. The designed detention basins are capable of capturing up to 65% of runoff to make the catchment safe from the flooding incidents.